Detailed Mineralogical and Petrographic Analysis of the Caprock from a Natural CO2 Occurrence in Hungary. (July 2017) - Király, Csilla; Szamosfalvi, Ágnes; Zilahi-Sebess, László; Sendula, Eszter; Kovács, István; Kónya, Péter; Udvardi, Beatrix; Szabó, Zsuzsanna; Szabó, Csaba; Falus, György
Abstract: The caprock is the only physical barrier in the migration path of CO2 during CO2 geological storage. For this reason, caprock integrity is one of the most important factors regarding the long-term safe underground storage of CO2 . As a result of geochemical reactions, among the caprock minerals and CO2 saturated pore water, the physical properties of caprocks such as porosity and permeability may change, which could affect their sealing capacity. Natural CO2 occurrences can help to understand these long-term reactions under storage conditions on geological timescale.